Decapod crustacean larvae dynamics in the west continental coast of Portugal: the region adjacent to Aveiro coastal lagoon as model - Bartilotti, Cátia Alexandra Vieira (2010)
Present thesis pretends to describe the horizontal and vertical distribution patterns of decapod crustacean larvae in the Portuguese upwelling ecosystem. The studied taxa were retained close to their parental populations; so, species from the inner shelf had their larvae concentrated close to the shore, species from the shelf had their larvae over the shelf, and the slope species had their larvae along the shelf break. The ontogenetic vertical distribution was also analysed, and the average depth of distribution of the larval stages varied through the larval development. The majority of the studied species had their early zoeal stages more close to the surface and the last zoeal stages in a more deep position. The morphological larval descriptions from laboratory cultured material of the three selected larval forms of decapod larvae are presented: the larval development of two closely related species of Lysmata, L. galapagensis e L. moorei (caridean shrimps), the complete larval developments of Clibanarius aequabilis and C. erythropus (hermit crabs), and the complete larval development of the crab Ilia nucleus.